Helminth products modulate innate immune recognition of nucleic acids in systemic lupus erythematosus. (April 2022) - Dall, Laura B; Deleuran, Bent; Østergaard, Lars J; Mardahl, Maibritt; Denton, Paul W; Nejsum, Peter
Aim: Current treatment of Systemic Lupus Erythematosus (SLE) is suboptimal and causes broad immunosuppression. Therapeutic use of helminths or helminth products has been suggested for autoimmune diseases such as SLE. In the present study, we evaluated possible immunomodulating effects of adult body fluid (ABF) from Ascaris suum on peripheral blood mononuclear cells (PBMCs) from SLE patients in an ex vivo setup. Methods: PBMCs from SLE patients and healthy controls (HC) were isolated and stimulated ex vivo with ABF and Toll-like receptor agonists or activators of the stimulator of interferon genes (STING) or mitochondrial antiviral signaling protein (MAVS) pathways. After 24 h of incubation, the cytokine profile was analyzed using ELISA and Meso Scale Discovery techniques. Results: ABF suppressed production of IL-6, TNF-α, CXCL10, and IL-10 by PBMCs from SLE patients and HCs following stimulation with specific agonists. ABF also reduced IFN-у production by stimulated PBMCs from HCs. Conclusions: Our data show that ABF has an immunomodulatory effect on the production of key cytokines in the pathogenesis of SLE. These results suggest that ABF or ABF components hold potential as a novel treatment option for SLE.